PENGEMBANGAN PEMBELAJARAN INQUIRY BERVISI SETS PADA SISTEM PENCERNAAN UNTUK MENINGKATKAN KECERDASAN EMOSIONAL DAN PRESTASI BELAJAR - Trimo Susilo (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT Attention to the issue of education is still lacking emotional intelligence development, but success is not determined by intelligence (IQ) alone, but rather by the emotional intelligence (EQ). Science learning process using appropriate methods and approaches can improve emotional intelligence. Therefore the development of research inquiry learning SETS vision on the concept of the digestive tract. The purpose of research for new product development, testing the validity and effectiveness of the product in improving EQ and student achievement. Research methods research and development (R and D). Limited scale test was conducted in a classroom, using one single shot design case study. Large scale test was conducted in a control class, and two experimental class, using pretest-posttest designs control group. Research subjects in class XI Science SMAN 3 Pekalongan. Test results show a valid product (criterion> 0.81), the percentage achieving grades EQ experimental class > class control. T test results showed t = 42.681 > t table = 2.025. Achievement of learning experimental class > class control. Conclusions of research, product development of valid and effective for improving EQ and student achievement. Products recommended to be a reference device development and learning to improve student achievement EQ. Keywords: Learning Inquiry, SETS, Emotional Intelligence